Turystyka ekstremalna vs. sporty ekstremalne = Tourism extreme vs. extreme sports - Marcin Sekida; Ewa Malchrowicz-Mośko (Kazimierz Wielki University, 2016)
Sekida Marcin, Malchrowicz-Mośko Ewa. Turystyka ekstremalna vs. sporty ekstremalne = Tourism extreme vs. extreme sports. Journal of Education, Health and Sport. 2016;6(12):666-679. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.221369 http://ojs.ukw.edu.pl/index.php/johs/article/view/4112         The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 754 (09.12.2016). 754 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.12.2016. Revised 20.12.2016. Accepted: 25.12.2016.       Turystyka ekstremalna vs. sporty ekstremalne Tourism extreme vs. extreme sports   Marcin Sekida Wydział Nauk Geograficznych i Geologicznych UAM w Poznaniu Ewa Malchrowicz-Mośko Wydział Turystyki i Rekreacji AWF w Poznaniu   Marcin Sekida Geographical and geological Department of Adam Mickiewicz University in Poznań Ewa Malchrowicz-Mośko Department of tourism and recreation ACADEMY in Poznań   Streszczenie: Turystyka ekstremalna jest zjawiskiem stosunkowo młodym, lecz bardzo dynamicznie rozwijającym się̨. W polskiej literaturze naukowej z zakresu turystyki można odnaleźć najczęściej jedynie wzmianki, że taki rodzaj turystyki faktycznie istnieje. Celem artykułu jest charakterystyka zjawiska turystyki ekstremalnej na tle polskiego piśmiennictwa z określeniem zależności pomiędzy tą formą podróżowania, a zjawiskami pokrewnymi, m.in. turystyką aktywną, kwalifikowaną i usportowioną. Celem artykułu jest również określenie podobieństw i różnic pomiędzy turystyką ekstremalną a sportami ekstremalnymi, ponieważ terminy te często traktowane są synonimicznie.   Abstract:             Extreme tourism is a relatively new phenomenon, but very fast developing. In Polish literature in the field of tourism can be found usually only mention that this type of tourism actually exists. The aim of the article is to characterize the phenomenon of extreme tourism on the background of Polish literature and relationships between this form of travel, and related phenomena, including active tourism, qualified tourism and sporting tourism. The aim of the article is also to determine the similarities and differences between the extreme tourism and extreme sports, as these terms are often treated synonymously.   Słowa kluczowe: turystyka ekstremalna, sporty ekstremalne, turystyka aktywna, turystyka kwalifikowana, turystyka usportowiona, turystyka szoku   Key words: extreme tourism, extreme sports, active tourism, qualified tourism, sporting tourism, shock tourism